Understanding the contract structure for mango and empirical analysis of its determinants. Issue 8 (3rd August 2015) - Ali, Jabir; Kumar, Sushil
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyze the structure of contractual arrangements in mango orchards and factors affecting the mango contract design in India. Design/methodology/approach – The study is based on personal structured questionnaire survey of 83 contractors in one of the major mango growing areas in India. A snowball sampling approach was adopted to select suitable respondents for the study. Descriptive statistics have been computed to understand the contractor's response on contract attributes. Factor analysis was used to categorize the contractors' responses on various attributes of the mango contract. Further, a logistic regression model has been developed to determine the factors affecting the contract decisions. Findings – The study identifies nine aspects of mango contracting covering orchard owner, orchard and contract management characteristics. Further, a logistic regression model has been developed to assess the factors affecting the contractor's decision on the time of entering into mango contracting, i.e. pre-flowering or post-flowering stage. Regression analysis results clearly indicate that contractors who prefer pre-flowering contracts pay significantly higher attention to contract management attributes. On the other hand, those contractors who normally enter in contract once the mango trees have flowered are more likely to pay attention to orchard-related features. Practical implications – Specifically, the results have implications for contract terms, contract efficiency and effectiveness and overall performance. Finally, the study provides suggestions for a future research agenda to analyze mango production contracts. Originality/value – Though contracting in mango growing is a common phenomena, there is limited analysis on identifying the key contract attributes and factors affecting the contract structure.